INTERNATIONAL EXPERIENCE IN ENSURING THE SECURITY OF DIPLOMATIC STRUCTURES: AN ANALYSIS OF THE ORGANIZATIONAL AND LEGAL MECHANISM - Volkov, I. (Honor and Law, 2020)
One of the negative trends in the development of international relations at the beginning of the XXI century can be considered the exacerbation of the problem of ensuring the security of foreign diplomatic bodies of accrediting states that operate in individual host countries. Such bodies primarily include diplomatic missions (embassies, missions) and consulates. Improper implementation of the commitments under the Vienna Conventions on Diplomatic Relations and Consular Relations sometimes causes misunderstandings and aggravation of interstate relations, which is detrimental to various aspects of foreign policy. The experience of public administration in the field of security of diplomatic facilities has been gained over many years of diplomatic activity and foreign policy relations in many democracies, which have a long history of state formation. These include the United States, Canada, Western Europe. There is some experience of such activities in Ukraine as well. Given the trends of constant development and transformation of interstate relations and changes taking place in the domestic political life of the state, it is seen that the issue of improving the security of diplomatic facilities will not lose its relevance in the near future. The purpose of the article is to analyze the international experience in the field of security of diplomatic structures, preparation of generalized conclusions on the organizational and legal mechanism of public administration in this area. The article summarizes and analyzes some documents of international legal nature, adopted in order to improve measures aimed at strengthening the protection, security and safety of diplomatic and consular missions and representatives. The analysis of experience of foreign states in the field of the organization of system of maintenance of safety of objects of diplomatic appointment is carried out. On the basis of the conducted research the general conclusions concerning the organizational and legal mechanism of public administration in this sphere are formulated. The researched experience can be used in further work for its adaptation at the organization of maintenance of safety of objects of diplomatic appointment of foreign states which are located in the territory of Ukraine.